Heavy Metal Contamination on Vannamei Shrimp Aquaculture in North Coast of Central Java - Apresia, Fadil; Ambariyanto, Ambariyanto; Yulianto, Bambang; Payus, Carolyn Melissa (Marine Science Department Diponegoro University, 2023)
The North Coast of Central Java receives consignments of waste containing heavy metal contamination from several sources, resulting in a decrease in water quality on the coast. Heavy metal contamination in water sources, such as Pb, Cd, and Cr that will be used in shrimp farming. The impact of Pb, Cd, and Cr can have several adverse effects, such as health risk, ecological imbalance, reduce shrimp growth and productivity, environment pollution. The research was conducted to analyze heavy metal contamination levels in ponds and vannamei shrimp yields on the northern coast of Central Java. The method involved collecting shrimp, water, and sediment samples at nine different locations (Dampyak; Suradadi; Kedongkelor; Danasari; Nyamplungsari; Pesantren; Depok; Wonokerto; Degayu). Heavy metal data were analyzed with SPSS. The mean lead concentrations were 0.52+0.19 mg.kg-1 in sediment, 0.66+0.11 mg.kg-1 in water, and 0.86+0.18 mg.kg-1 in shrimp. Cadmium levels were measured in soil (0.028+0.03 mg.kg-1), water (0.027+0.021 mg.kg-1), and shrimp (0.011+0.004 mg.kg-1). The mean chromium concentrations were 0.51+0.25 mg.kg-1 in sediment, 0.93+0.40 mg.kg-1 in water, and 0.95+0.11 mg.kg-1 in shrimp. Based on the calculation of the average BAF x > 1.0, vannamei shrimp on the northern coast of Central Java have the capability of becoming bioaccumulation and bioindicators. The consumption of vannamei shrimp for 70 years has a lifetime risk of developing cancer due to the LCR value of x > 10-6 on the northern coast of Central Java.